Existing and Emerging Covariates of Iris Recognition - Kumar, Sunil; Lamba, Vijay Kumar; Jangra, Surender (International Journal of Computer Sciences and Engineering, 2019)
Iris as a biometric trait has established itself in last two decades. Iris being unique and reliable is used for recognition and authentication purpose instead of using Passwords and PINs. Security is a major concern in any recognition system so is the case with iris recognition system. Further, recognition performance depends upon many factors among which distance, lighting conditions, subject cooperation, and pupil dynamics to name some important ones. The above mentioned covariates have been studies vastly in reference to iris recognition. In this paper, we have considered various novel factors that affect the performance of iris recognition system. Pupil dilation, contact lenses, periocular recognition, template aging, use of drugs and alcohol and sensor interoperability have been under investigation as emerging covariates of iris recognition; in recent times. The focus of this paper is to present a review of various covariates (existing as well as emerging) and their effects on recognition performance. This work shows that these covariates have considerable effect on iris recognition performance and need to be considered while implementing any commercial iris recognition systems.